The challenges in implementing EMR system in private hospital: an empirical study in Malacca State/ Muhammad Luqman Alif Ismail...[ et al. ] - Ismail, Muhammad Luqman Alif; Amran, Noradawiyah Yasmin; Iberahim, Nurulaida; Mohd Yusop, Siti Khursiyah (2014)
The objective of the study was to empirically identify the challenges that related to the implementing Electronic Medical Records System (EMRS) in private hospital in Malacca state. EMRS is a tool that could help and assist staff and health care professionals in completing their task. The ENIRS also has the potential to aid health care professionals with easier access about the patient's information. Moreover, the system also assists in managing and controlling the records in the department and the hospital or medical institution for overall. The function of EMRS also broad and can be used by other department, not specifically for medical records department only. The entire department within the hospital or health care organization can used system as their tools in managing and controlling the records in their department. This is to avoid and prevent missing or misplace file in the organizations. However, in implementing EMRS, there were occur some challenges during the implementation process. So, the researchers take this opportunity to do a research on what are the challenges that faced by private hospital in Malacca state in implementing EMRS in their hospital. This is because private hospital in Malacca is not fully implementing EMRS and this situation could lead to unwilling problem in future. Staffs and health care professionals in the private hospital realized the benefits and advantages if the hospital uses system in their tasks and activities, but, the desire on themselves in learning the system in less. This is because they too comfortable in 'manual zone' which is they used to do manual method in manage all the records and they did not want to explore more to the system because for them, it will wasting their time and they cannot fully understand how to use and run the system. The sample for this study was derived using simple sampling by 47 participants which the entire record department staffs if 3 private hospitals in Malacca state. Likert scale questionnaire served as the method of data collection. The researchers use online questionnaires to collect data. This is because the limitation of time and redundant time between the researchers and the participants, so online questionnaires been use to collect data. The data collection will determined the challenges associated with EMRS implementation. Recommendations for future researcher are also presented.